A Study of the Relationship between Physical Activity and Anxiety and Depression in High Academic Pressure College Students - Wang, Chenyu; Luo, Jiong (Quality in Sport, 2025)
Objective: To examine the relationship between physical activity and anxiety and depression among college students experiencing high academic pressure.Methods: A stratified sampling method was used to select 1051 college students. Their physical activity, anxiety, and depression were measured using the International Physical Activity Scale (IPAQ-SF), Generalized Anxiety Scale (GAD-7), and Symptom Self-assessment Scale (SCL-90), respectively. Data were analyzed with SPSS 21.0.Results: 1. Physical activity was generally insufficient among high academic pressure college students, with significant gender differences (p < 0.05), as male students had higher activity levels than females. 2. Anxiety was present in 73.7% of these students, with significant differences in anxiety distribution by gender, only-child status, and single-parent family background (p < 0.05). 3. Depressive mood was found in 91% of students, with significant gender differences (p < 0.01). 4. There was a highly significant difference in depressive mood across different physical activity levels (p < 0.01). Physical activity had a negative correlation with depression (r = -0.062, p < 0.05), while anxiety and depression were significantly positively correlated (r = 0.608, p < 0.01). Academic pressure also had significant positive correlations with both anxiety and depression (r = 0.344, r = 0.325, p < 0.01).Conclusions: High academic pressure college students tend to be physically inactive and have high prevalence rates of anxiety and depression. Although physical activity does not appear to reduce anxiety or academic pressure directly, it significantly alleviates depressive symptoms, especially at higher intensity levels.